Peg‐interferon alpha add‐on Tenofovir disoproxil fumarate achieved more HBsAg loss in HBeAg‐positive chronic hepatitis B naïve patients. Issue 10 (14th July 2021) - Li, Jing; Qu, Lihong; Sun, Xuehua; Liu, Yanhong; Gong, Qiming; Yu, Demin; Zhang, Donghua; Jiang, Jiehong; Chen, Jia; Wei, Dong; Han, Yue; Gao, Yueqiu; et al.
Abstract: Several studies have showed that combining peg‐interferon alpha (Peg‐IFNα) with nucleotide analogues has complementary effects in chronic hepatitis B (CHB), but the optimal regimen and potential mechanisms remain unclear. This was a prospective, longitudinal and multicentre clinical trial (NCT03013556). HBeAg‐positive CHB naïve patients were randomly assigned to three groups: tenofovir disoproxil fumarate (TDF) monotherapy for 96 weeks, TDF alone for 48 weeks and sequentially Peg‐IFNα added for 48 weeks, TDF de novo combination with Peg‐IFNα for 48 weeks then TDF alone for 48 weeks. The primary endpoint was HBeAg seroconversion at week 96 and HBsAg loss as the secondary endpoint. Furthermore, the levels of 12 cytokines in serum were assessed at different time points. A total of 133 patients were included in the analysis. The rates of HBeAg seroconversion at 96 weeks were not significant different among the three groups ( p = 0.157). Interestingly, patients in the Peg‐IFNα add‐on group showed markedly lower HBsAg level compared with the other two groups at week 96. In addition, only three patients in the Peg‐IFNα add‐on group achieved HBsAg loss. For the following 24 weeks from week 96, no HBsAg reappearance in the three patients and no new patients with HBsAg loss were observed in the three groups. Serum cytokine analysis showed that the baseline level of interferon‐inducible protein‐10 (IP‐10) was strongly higher in HBeAg conversion patients and HBsAg loss patients. Compared with de novo combination and TDF alone, the addition of Peg‐IFNα in TDF‐treated group might be an effective strategy for HBsAg loss in HBeAg‐positive CHB naïve patients.